A teologia do laicato na constituição dogmática Lumen gentium e nas conferências gerais do Episcopado da América Latina - Lopes, Leandro José (2012)
This dissertation analyses the theological conception of Christian laymen of the Catholic Church language and doctrine. Part of ecclesiology as the theological place of constant existence of laity in the ecclesial tradition, analyzing the historical and theological factors, in which nuances are evidenced in form and degree of involvement of lay members in Church`s mission. From this dialectic perspective, by the nature of ecclesiology because of the invisible and visible dimension of Church as the only reality in history, the phenomenon of the Catholic Action to comprehend the pastoral and theological horizon of council priests in the Council Vatican II was studied. Contextualization properly given, historical and theological of the council event, the interpretation of IV chapter of Dogmatic Constitution Lumen Gentium about the Church was developed, in which is explained the theological dogmatic nucleus about the laity of the Catholic Church. Once this theological nucleus was identified, conclusive texts of General Conferences of the Episcopate of Latin America CELAM, were analyzed, ascertaining its respective theological development, in which it is found the integral perception, but gradual of conception of Christian laymen emitted by Vatican Council II. This graduallity means that the conferences accentuate some theological aspects about laymen, in consonance with the challenges of the evangelizing mission of Church in Latin America`s reality. In the entirety of the dissertation, the secular vocation of the laity can be evidenced as one advance of Vatican Council II and the respective effort of CELAM conferences in effect it ecclesially.